Implementation of an information system for tuberculosis in healthcare facilities in Indonesia: evaluation of its effectiveness and challenges - Rita Dian Pratiwi; Bachti Alisjahbana; Yanri Wijayanti Subronto; Sigit Priyanta; Suharna Suharna (Archives of Public Health)
Abstract Background Tuberculosis (TB) surveillance in Indonesia is currently supported by the recording and reporting technology Tuberculosis Information System (Sistem Informasi Tuberkulosis [SITB]). SITB is used by all health workers responsible for TB programs in health facilities or hospitals throughout Indonesia. The satisfaction and ease of use of SITB affect the speed and accuracy of TB case reporting. Therefore, evaluating the information system’s quality is crucial. SITB utilization is comprehensively assessed using the End-User Computing Satisfaction (EUCS) method, which considers the dimensions of content, accuracy, timeliness, and ease of use. Furthermore, the effectiveness of the user interface using heuristic evaluation methods is critical. The primary objective of this study is to conduct a comprehensive evaluation of the System for Information on Tuberculosis (SITB) focusing on its usability and user satisfaction. Methods This study employed a multi-method design approach. First, a heuristic evaluation was conducted by three expert user experience designers. Second, a cross-sectional survey of 115 SITB users was carried out across all health facilities in the Special Region of Yogyakarta, Indonesia, for reporting TB cases, using the EUCS method. Finally, in-depth interviews were conducted in 10 health facilities, focusing on identifying specific attributes that needed improvement to enhance user satisfaction. Results The evaluation indicated that user convenience and timeliness require improvement, as well as the match between the system and the real world and error prevention, as shown in the heuristic evaluation of the SITB user interface. These findings were confirmed through interviews that identified the need for user manuals, server repairs, and information and SITB forms that are suitable for TB management in the field. The overarching assessment of the SITB reveals persistent challenges in data entry, attributed to the functionality of the application, thereby potentially impacting user satisfaction. Conclusions SITB application requires “major” improvements to make recording, reporting, and tracing activities more efficient and precise. Moreover, the integration of existing information systems in healthcare facilities is essential to support the tuberculosis surveillance reporting system in Indonesia.